The Effect of Financial System Digitalization on the Accuracy of Financial Statements with Human Resource Competence as a Moderation Variable at Bank Sumut - Fricillia Vina Cindy Tioria; Renny Maisyarah; M. Irsan Nasution (Equivalent : Journal of Economic, Accounting and Management, 2026)
This research aims to examine the impact of financial system digitalization on financial statement accuracy, with human resource competence serving as a moderating variable, at Bank Sumut. Utilizing a quantitative approach with a survey method, data was collected through a Likert scale questionnaire from 50 respondents consisting of key personnel in financial management. The analysis was performed using SEM-PLS to evaluate direct and moderating relationships. The results show that digitalization of financial systems significantly affects financial statement accuracy, confirming the positive influence of technology integration on reporting accuracy. However, the competence of human resources did not have a significant direct effect on the accuracy of financial reports. Furthermore, the moderating effect of human resource competence was found to be non-significant in strengthening the relationship between digitalization and financial reporting accuracy. These findings suggest that while digitalization plays a crucial role in improving financial reporting, the competence of human resources, although important, may not be a decisive factor in enhancing the impact of digitalization. This study contributes to understanding the role of technology in enhancing financial transparency and reporting accuracy, with implications for bank management and policymakers in the digital era.